2006
DOI: 10.1111/j.1365-2893.2006.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of vascular endothelial growth factor in small hepatocellular carcinoma

Abstract: Vascular endothelial growth factor (VEGF) is involved in both development and progression of several epithelial tumours, but its role in hepatocellular carcinoma (HCC) is unclear. Assessment of liver and blood levels of VEGF may provide further insights on angiogenesis in HCC. Tissue mRNA of VEGF-165, VEGF-189 and their receptor KDR was assessed by a semi-quantitative retro-transcriptase polymerase chain reaction, and expressed as target transcript/beta-actin ratio, in 29 patients with HCC, 26 with cirrhosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…The presence or absence of airway inflammation induced by elastase instillation may account for the differential mobilization of VEGF between the protocols. Previous reports suggested that the VEGF concentration gradients in vivo may promote local enhancement of angiogenesis (13,14,21). It was interesting that VEGF concentration gradients between the lung and circulation appeared to be enhanced by SS in our murine emphysema model.…”
Section: Discussionsupporting
confidence: 48%
“…The presence or absence of airway inflammation induced by elastase instillation may account for the differential mobilization of VEGF between the protocols. Previous reports suggested that the VEGF concentration gradients in vivo may promote local enhancement of angiogenesis (13,14,21). It was interesting that VEGF concentration gradients between the lung and circulation appeared to be enhanced by SS in our murine emphysema model.…”
Section: Discussionsupporting
confidence: 48%
“…35,36 Similar findings in other studies have laid the groundwork for using VEGF activity as a tool to screen for both premalignant liver lesions and invasive HCC. 37,38 In the first study, 37 tissue mRNA level of VEGF-165 was assessed by a semiquantitative reversetranscriptase polymerase chain reaction in 29 patients with HCC, 26 with cirrhosis, and 15 with chronic hepatitis. The liver expression of mRNA of VEGF-165 was found to be significantly higher in HCC than in chronic liver diseases and in the cirrhotic tissue of HCC patients than in those with HCC-free cirrhosis.…”
Section: Molecular Interactions With Vegfmentioning
confidence: 99%
“…More recently Fernandez et al (37) showed in portal vein ligated rats that treatment with rapamycin (VEGF signaling inhibitor) and Gleevec (PDGF signaling inhibitor) reduced splanchnic neovascularization and significantly decreased portal pressure. Furthermore, Iavarone et al (38) showed a significant VEGF gradient between hepatic vein and peripheral vein serum levels that correlated with the degree of hepatic vein pressure gradient (HVPG) in hepatocellular carcinoma (HCC)-free patients. Interestingly, such association was not found in patients with cirrhosis and HCC, suggesting, that in these patients serum levels of VEGF were mainly influenced by VEGF synthesis by neoplastic liver cells rather than by portal hypertension.…”
Section: Discussionmentioning
confidence: 99%